2022
DOI: 10.1021/acs.jpcc.2c03481
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Magnetic Properties in Zero-Dimensional (H2DABCO)MX4·nH2O (M = Mn and Cu; X = Cl and Br; n = 0, 1, and 4)

Abstract: We report five new manganese and copper organic–inorganic hybrid (OIH) halides based on 1,4-diazabicyclo[2.2.2]­octane (DABCO: C6H12N2). The materials obtained have general formula (H2DABCO)­MX4·nH2O where M = Mn and Cu, X = Cl and Br, and n = 0, 1, and 4. The compounds (H2DABCO)­MnX4·4H2O (X = Cl and Br) crystallize in a chiral P212121 structure with unique zero-dimensional (0D) manganese octahedra, whereas anhydrous (H2DABCO)­MnBr4 exhibits a monoclinic crystal structure (space group P21/c) with isolated MnB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…In contrast, compound 2 does not order down to 1.8 K (Figure d), indicating the paramagnetic nature. The obtained θ CW of 1.5 K and magnetic field-dependent isotherms are consistent with the paramagnetic compounds (Figure d,e) . Since compound 1 consists of 1D infinite chains, the magnetic ordering might occur by interchain interaction, which is mediated by two halides pathway (Mn–Cl···Cl–Mn), where the Cl···Cl distance is about 4.321 Å .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, compound 2 does not order down to 1.8 K (Figure d), indicating the paramagnetic nature. The obtained θ CW of 1.5 K and magnetic field-dependent isotherms are consistent with the paramagnetic compounds (Figure d,e) . Since compound 1 consists of 1D infinite chains, the magnetic ordering might occur by interchain interaction, which is mediated by two halides pathway (Mn–Cl···Cl–Mn), where the Cl···Cl distance is about 4.321 Å .…”
Section: Resultssupporting
confidence: 82%
“…In addition, the cell parameter b gets doubled in LTP compared to RTP, consistent with the order–disorder transition. To understand the additional role of SPT, we have calculated the bond length (Δ d ) and bond angle (σ oct 2 ) distortion parameters using the formula normalΔ d = ( 1 n ) n true[ d n d av d av true] 2 and σ oct 2 = 1 11 i = 1 12 false[ α i 90 false] 2 . In RTP, the Δ d and σ oct 2 are 9.38 × 10 –5 and 51.97, respectively, revealing that compound 1 is associated with moderate distortion.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some investigations demonstrated that the emission in Mn 2+ -tetrahedra-based OIH compounds results from the recombination of self-trapped excitons (STEs). STEs are Frenkel-like bound excitons trapped in a deformable lattice and result from the synergistic effect of reduced lattice dimensionality, structural distortion, lattice softness, and halogen vacancies. In such compounds, a longitudinal optical phonon scatters the charge carriers and restricts its delocalization via Fröhlich interaction, leading to the formation of STEs. , However, the Mn 2+ octahedral emission shows a larger Stokes shift and a broader emission band compared to the Mn 2+ tetrahedral emission, indicating the possibility of STE recombination in the octahedral emission. , In this paper, we report evidence for STE emission in an Mn 2+ -octahedra-based OIH halide, (Guanidinium) 6 Mn 3 Br 12 [GuMBr], which crystallizes in a trimeric zero-dimensional (0D) structure and exhibits intense red emission with a large Stokes shift, a broad emission band, and long-lived photoexcited electrons. Analysis of the temperature-dependent photoluminescence (PL) line width and Raman spectra confirms electron–phonon coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Although the line width and peak shape did not change with increasing temperature, the intensity deteriorated. This is the thermal quenching effect and can be understood using the Arrhenius model: 49 Here I 0 and I T are the emission intensities measured at 300 K and temperature T . A is the ratio of the nonradiative rate to the radiative rate and termed as the quenching frequency factor.…”
Section: Resultsmentioning
confidence: 99%
“…Although the line width and peak shape did not change with increasing temperature, the intensity deteriorated. This is the thermal quenching effect and can be understood using the Arrhenius model: 49 ln…”
Section: Temperature-dependent Photoluminescencementioning
confidence: 99%